A justiça constitucional na democracia: a busca da legitimidade substantiva - Rodrigues, Douglas Alencar (2022)
In the past years, the Brazilian society, somewhat perplexed and confused, has been witnessing a political landscape of substantial growth of power in the judicial branch in detriment of the other branches of government power. Public attention shifts with special emphasis to the Supremo Tribunal Federal, the highest level of the judicial system and the main responsible for the protection of the Constitution. Highly complexe matters, such as moral affairs and public policies related to fundamental rights of different natures are constantly being submitted to the courts judgement, in what it is being called the judicialization of life, politics and social relations. This new reality, marked by the taking of this new role by STF, puts in perspective not only the question of the ressignification of the concept of democracy, founded on the idea of “majoritarianism”, and judicial review legitimacy, but also the need to find some kind of mechanism that is able to confer subjective legitimacy to STF’s decisions, while the political process is not refined and political prominence is not given back to its rightful owner. This research aims to examine this new institucional context, discussing the basis of judicial review legitimacy and proposing a way of reestablishing harmony between democracy and judicial review. The final proposal of this work involves the creation of a referendum procedure for decisions reputed to be sensitive, at the discretion of the other Powers, as a way of re-establishing the connection between the reading of the Constitution and the will of the holder of sovereignty. From the methodological point of view, a qualitative approach was adopted, based on bibliographic and documental research, with the examination of specialized literature and the analysis of several decisions handed down by the STF